Electricity savings by implementing energy efficiency standards and labels for clothes washers in Malaysia - Saleh, A.A.; Asri, M.; Sinin, Hamdan (School of Engineering, Taylor’s University, 2011)
Clothes washers being one of the energy consuming household appliances in Malaysia have become a target for energy efficiency improvements. In the present study, a series of experiment investigations have been conducted on six clothes washers of varying capacities. The objectives are to develop the standards and labels. The test has been performed according to IEC (International Electrotechnical Commision) clothes washers test specification. Using the experimental data, a baseline standard has been developed by statistical method. From the baseline standards, 10% standards have been developed. The baseline unit energy consumption was calculated to be 32 Wh/kg/cycle (average unit energy consumption of the six models) and on the basis of baseline unit, standard unit energy consumption had been proposed to be 29 Wh/kg/cycle. It has been estimated with the introduction of minimum energy efficiency standards for clothes washer 38077037.46 kWh of energy could be saved per year. To develop a comprehensive energy guide labels, three labels had been design, which were star labeling, speedometer labeling and letter bin labeling. A survey was conducted with three different types of labels among the consumers and with the surveys respond, energy guide label of household clothes washers has been proposed for Malaysia. This is result from used of energy-efficient appliances product and is well positioned to promote more widespread efficient improvement.